Hyperurechemia and Arterial Mutual Risk Factors for Hypertension - Abdullaev J. U. (Scholars Digest Publishing, 2023)
The results of a number of studies indicate that HY is a predictor of the development of cardiovascular events and death in patients with hypertension and congestive heart failure, and, apparently, can be considered as an independent risk factor for cardiovascular complications. According to a number of authors, the frequency of hypertension in patients with GU ranges from 36 to 58%, and in combination with metabolic syndrome increases to 72%.
Keywords: hyperurekemia, arterial hypertension, risk factors, cardiovascular pathology.